Statin use and risk of multiple myeloma: An analysis from the cancer research network. Issue 3 (15th May 2017) - Epstein, Mara M.; Divine, George; Chao, Chun R.; Wells, Karen E.; Feigelson, Heather Spencer; Scholes, Delia; Roblin, Douglas; Ulcickas Yood, Marianne; Engel, Lawrence S.; Taylor, Andrew; Fortuny, Joan; Habel, Laurel A.; et al.
Abstract : Animal and human data suggest statins may be protective against developing multiple myeloma; however, findings may be biased by the interrelationship with lipid levels. We investigated the association between statin use and risk of multiple myeloma in a large US population, with an emphasis on accounting for this potential bias. We conducted a case‐control study nested within 6 US integrated healthcare systems participating in the National Cancer Institute‐funded Cancer Research Network. Adults aged ≥40 years who were diagnosed with multiple myeloma from 1998–2008 were identified through cancer registries ( N  = 2, 532). For each case, five controls were matched on age, sex, health plan, and membership duration prior to diagnosis/index date. Statin prescriptions were ascertained from electronic pharmacy records. To address potential biases related to lipid levels and medication prescribing practices, multivariable marginal structural models were used to model statin use (≥6 cumulative months) and risk of multiple myeloma, with examination of multiple latency periods. Statin use 48–72 months prior to diagnosis/index date was associated with a suggestive 20–28% reduced risk of developing multiple myeloma, compared to non‐users. Recent initiation of statins was not associated with myeloma risk (risk ratio range 0.90–0.99 with 0–36 months latency). Older patients had more consistent protective associations across all latency periods (risk ratio range 0.67–0.87). Our results suggest that the association between statin use and multiple myeloma risk may vary by exposure window and age. Future research is warranted to investigate the timing of statin use in relation to myeloma diagnosis. Abstract : What's new? Statin use may protect against multiple myeloma, depending on when they are taken. Previous results have suggested that statins may protect against various cancers, including hematological malignancies. This study focused on long‐term statin use, asking whether myeloma risk changed with multiple years' use of the popular cholesterol‐lowering medications. The authors collected data on a large US population, and found that using statins for at least 5 years did appear to reduce risk of multiple myeloma, possibly by 20–28%. Shorter periods of use, however, did not seem to guard against the cancer.